In situ passivation of GaAsP nanowires. (15th November 2017) - Himwas, C; Collin, S; Rale, P; Chauvin, N; Patriarche, G; Oehler, F; Julien, F H; Travers, L; Harmand, J-C; Tchernycheva, M
Abstract: We report on the structural and optical properties of GaAsP nanowires (NWs) grown by molecular-beam epitaxy. By adjusting the alloy composition in the NWs, the transition energy was tuned to the optimal value required for tandem III–V/silicon solar cells. We discovered that an unintentional shell was also formed during the GaAsP NW growth. The NW surface was passivated by an in situ deposition of a radial Ga(As)P shell. Different shell compositions and thicknesses were investigated. We demonstrate that the optimal passivation conditions for GaAsP NWs (with a gap of 1.78 eV) are obtained with a 5 nm thick GaP shell. This passivation enhances the luminescence intensity of the NWs by 2 orders of magnitude and yields a longer luminescence decay. The luminescence dynamics changes from single exponential decay with a 4 ps characteristic time in non-passivated NWs to a bi-exponential decay with characteristic times of 85 and 540 ps in NWs with GaP shell passivation.